SINs and SOMs: neural microcircuits for size tuning in the zebrafish and mouse visual pathway - Barker, Alison J.; Baier, Herwig (Frontiers in Neural Circuits, 2013)
In many animals, a fast and reliable circuit for discriminating between predator-sized objects and edible (prey-sized) objects is necessary for survival. How are receptive fields in visual brain areas organized to extract information about size? Recent studies from the zebrafish optic tectum and the mouse visual cortex suggest de novo shaping of receptive fields by subtypes of inhibitory neurons. Del Bene et al. (2010) describe a population of GABAergic neurons in the zebrafish optic tectum (Superficial Interneurons, SINs) that are necessary for size filtering during prey capture. Adesnik et al. (2012) describe a somatostatin-expressing interneuron population (SOMs) that confers surround suppression on layer II/III pyramidal cells in mouse V1. Strikingly both the SINs and the SOMs, display size-dependent response properties. Increasing visual stimulus size increases excitatory input to these neurons. Dampening SIN or SOM activity alters tuning of neighboring circuits such that they lose preference for small objects. Both results provide exciting evidence for mechanisms of size filtering in visual circuits. Here we review the roles of the SINs and the SOMs and speculate on the similarity of such spatial filters across species.